Engineering & architectural science - 2 (a multidiscipliner approach) - Yavuz, Özerk; Dönmez, Mustafa Alper (Ankara: Astana Yayınları, 2022)
ENGINEERING ; ARCHITECTURAL SCIENCE - 2 (A MULTDISCIPLINER APPROACH) (e-kitap)
2
Keywords: Mühendislik